2017
DOI: 10.1371/journal.pone.0173256
|View full text |Cite
|
Sign up to set email alerts
|

Household air pollution from use of cooking fuel and under-five mortality: The role of breastfeeding status and kitchen location in Pakistan

Abstract: Household air pollution (HAP) mainly from cooking fuel is one of the major causes of respiratory illness and deaths among young children in low and middle-income countries like Pakistan. This study investigates for the first time the association between HAP from cooking fuel and under-five mortality using the 2013 Pakistan Demographic and Health Survey (PDHS) data. Multi-level logistic regression models were used to examine the association between HAP and under-five mortality in a total of 11,507 living childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 36 publications
9
65
0
Order By: Relevance
“…However, the present study found that predominant breastfeeding was associated with a lower odds of infants to experience diarrhoea in Ethiopia. Our finding was consistent with studies conducted in sub-Saharan African [11,13,15] and South Asian countries [39,40], which showed that predominant breastfeeding was associated with a lower risk of diarrhoea in children. Despite the variations in the literature on the health effect of predominant breastfeeding, some authors have argued that promoting both EBF and predominant breastfeeding may be beneficial to the infant as some studies found lower risk of ARI and diarrhoea among predominantly breastfed infants [11,13].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…However, the present study found that predominant breastfeeding was associated with a lower odds of infants to experience diarrhoea in Ethiopia. Our finding was consistent with studies conducted in sub-Saharan African [11,13,15] and South Asian countries [39,40], which showed that predominant breastfeeding was associated with a lower risk of diarrhoea in children. Despite the variations in the literature on the health effect of predominant breastfeeding, some authors have argued that promoting both EBF and predominant breastfeeding may be beneficial to the infant as some studies found lower risk of ARI and diarrhoea among predominantly breastfed infants [11,13].…”
Section: Plos Onesupporting
confidence: 92%
“…In the current study, households that used electricity, natural gas, biogas, or kerosene as a cooking fuel were classified as 'improved', while those households that used charcoal, firewood, or dung were grouped as 'not improved'. This classification was based on previously published studies conducted in LMICs [39][40][41].…”
Section: Potential Confoundersmentioning
confidence: 99%
“…was not certified by peer review) (which The copyright holder for this preprint this version posted November 2, 2019. . https://doi.org/10.1101/19010801 doi: medRxiv preprint on their mother's back or placed to sleep or stand beside their mother when they are cooking because this is common practice in South-East Asian countries, including Myanmar (20,21,32,34).…”
Section: Exposuresmentioning
confidence: 99%
“…12,13 It is also shown that the kind of cooking fuel used at the household influences the incidence of ARI in children. [14][15][16] In Ethiopia, according to the Ethiopian demographic and health survey (EDHS), the prevalence of ARI in children under five years of age was 13% in 2005, and the magnitude reduced to 7% in EDHS 2011, however, the prevalence remained 7% in EDHS 2016. Despite the persistent higher prevalence of ARI among children in Ethiopia, contributing factors for the disease were not well explored.…”
Section: Introductionmentioning
confidence: 99%